Sexagem de embriões bovinos produzidos in vitro com sêmen selecionado por Percoll ou Swim-up - Wolf, Caroline Antoniazzi (2007)
Preimplantation genetic diagnosis (PGD) is becoming a current issue in animal reproduction biotechnology due to economical reasons. Predetermining the sex of offspring is one example of PGD. This study aimed to determine the percentage of male and female bovine embryos in vitro produced after oocyte fertilization with Percoll density gradient centrifugation or with self-migration (swim-up) selected semen. In experiment 1, sperm selection was performed by 90%-45% discontinuous Percoll density gradient centrifugation (T1) and swim-up (T2). In experiment 2, along side the discontinuous gradient, a 67.5% continuous density gradient, and centrifugation time of 5 and 10 minutes were used. A total of 4 treatment groups was defined (TI = continuous, 5 minutes, TII = discontinuous, 5 minutes, TIII = continuous, 10 minutes and TIV = discontinuous, 10 minutes). Polymerase chain reaction (PCR) was used to determine the sex of the embryos. T1 (n=185) resulted in 48.65% (n=90) male embryos and 51.35% (n=95) female embryos and T2 (n=142) in 58.45% (n=83) male and 41.55% (n=59) female embryos. In experiment 2, the percentages of male and female embryos obtained in TI (n=93), TII (n=70), TIII (n=82) and TIV (n=82) were 49.46% (n=46) and 50.54% (n=47), 57.14% (n=40) and 42.86% (n=30), 36.59% (n=30) and 63.41% (n=52) and 48.78% (n=40) and 51.22% (n=42), respectively. There was no difference on the percentage of males and females in all treatment groups from experiments 1 and 2 when these were individually compared to the expected percentage of 50% of each sex. There was also no difference in male and female embryo percentage between treatment groups in experiments 1 and 2.